2009
DOI: 10.1111/j.1439-0396.2009.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effect of camel milk in alloxan-induced diabetic dogs: a dose-response experiment

Abstract: This study was conducted to evaluate the effect of camel milk in alloxan-induced diabetic dogs and to follow this effect at three doses of milk. Firstly, three groups of dogs were used: two groups composed each of four diabetic dogs and receiving raw camel milk (treatment 1) or cow milk (treatment 2), and four healthy dogs getting raw camel milk (treatment 3) were used as control. Each animal was treated with 500 ml of milk daily. Secondly, we compared the effects of three amounts of camel milk: 100 ml, 250 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 19 publications
(19 reference statements)
3
27
0
Order By: Relevance
“…; Sboui et al . ), and the findings of the present study are in agreement. We have shown that the administration of CM to STZ‐induced diabetic rats resulted in significant correction of the blood glucose and also improved the circulating levels of insulin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…; Sboui et al . ), and the findings of the present study are in agreement. We have shown that the administration of CM to STZ‐induced diabetic rats resulted in significant correction of the blood glucose and also improved the circulating levels of insulin.…”
Section: Discussionsupporting
confidence: 93%
“…; Sboui et al . ). For example, camel breeders in India who consume CM regularly have zero incidence of DM, as compared to 5.5% in other communities in which CM is not consumed (Agrawal et al .…”
Section: Introductionmentioning
confidence: 97%
“…Reports also claim that camel milk can cure severe food allergies in children unresponsive to more conventional treatments and aid in the management of diabetes and its complications . For example, in a dog model of alloxan‐induced diabetes, 3‐week consumption of camel milk resulted in a statistically significant decrease in blood glucose, total protein and cholesterol . Efficacy was dose‐related and glycemic control persisted for 2 weeks after the dogs stopped drinking camel milk.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of high concentration of insulin/insulin-like substances in camel milk such as half-cystine [15], the effect of small-sized immunoglobulins of camel milk on bcell [7] and the lack of coagulation of camel milk in the human stomach contribute to the hypoglycemic effect in type 1 diabetes in human [6], rats [99] as well as in alloxaninduced diabetic dogs [102].…”
Section: Camel Milk Adjuvant For Management Of Diabetesmentioning
confidence: 99%